A Study into the Implementation and Impact of the European Working Time Directive at Sheffield Teaching Hospitals NHS Foundation Trust - Fitch, Jane (2007)
Training grade doctors (junior doctors) have historically worked for extremely long hours in the interests of education and experience. This practice is unsafe for patients and doctors alike (it has been proven that tired doctors make more mistakes) and from a clinical risk management perspective has been deemed to be unsustainable. The New Deal (1991) was the first piece of agreed legislation (agreed by the Department of Health, Royal Colleges, and British Medical Association Junior and Senior Committees) that attempted to regulate this process. It imposed a reduction in the hours of work to a maximum average of 56 hours of work and 72 hours of duty by August 1996 (this was not achieved for the majority of junior doctors in practice). Health Service Circular (HSC) 1998/240 was issued to the NHS in December 1998 to clarify the regulations agreed in the New Deal and address any ambiguities, encouraging a consistent approach across NHS Trusts and NHS Task Forces. However,it was the European Working Time Directive (EWTD) 2004 and in particular HSC 2003/001 that made a reduction in hours a legal requirement for NHS Trusts and Foundation NHS Trusts - from 1 August 2004 all junior doctors had to be contracted to work a maximum average of 58 hours per week or they would be deemed to be in posts. Nationally, leading up to this deadline in 2004, there was a huge amount of organisational change that occurred in the working hours, duties, and working patterns of junior doctors (and in turn other NHS employees) as well as in service delivery in the wider health service as a whole. To date this is an area with little empirical research. Prior to 1 August 2004, many junior doctor rotas at Sheffield Teaching Hospitals NHS Foundation Trust (STHFT), the largest NHS Foundation Trust in England, were typically organised such that significant changes were required in order to become EWTD 2004 compliant. Consequently individual Directorates, as well as the organisation as a whole,underwent a series of major significant changes during this time. This study has investigated the implementation and impact of the EWTD at STHFT. In doing so it has answered the following questions: How was the EWTD implemented at STHFT in 2004? What was the impact of EWTD implementation in 2004?